Experimental Application Of Educational Infographic Based On Assure Model In Higher Education (Journal of Namibian Studies : History Politics Culture, 2023)
With the ASSURE Model, the current project aims to develop an academic design for experimental psychology for third-year Department of Educational and Psychological Sciences students. The study adopted a descriptive methodology to achieve this. The researcher considered the specifications for developing the designs and separated them into (19) sub-educational methods. It may have been a six-phase instructional design utilizing the ASSURE MODEL (Analyze learners, define objectives, Set objectives and standards, select strategies, technologies, media, and resources, use technologies, media, and materials, and so on. The use of resources, media, and technology demands student participation. Encourage student participation and feedback: review and assessment. In addition, educational infographics can provide information efficiently and abstractly by merging textual information with specific signs, achieving the goal of presenting taught courses visually via infographics, a modern tool. This experimental study aims to measure the impact of utilizing infographics in higher education to simplify information and increase students' attention. In this study, infographics lectures were involved in sampling students at Applied Sciences Private University in Jordan in selected colleges, Information Technology College and Business College, with an aim to encourage employing new educational techno-visual methods.